Pengembangan Model Pembelajaran Penjas Inovatif Berbasis Modifikasi Teknik Dasar Bulutangkis Untuk Meningkatkan Partisipasi Aktif Siswa - Muh Ishak; Awaluddin Awaluddin; M Imran Hasanuddin (PT Mediatama Zayna Indonesia, 2025)
This study aims to develop and test the effectiveness of an innovative Physical Education, Sports, and Health (PJOK) learning model based on modifications to basic badminton techniques to increase active participation of students at SMK Negeri 6 Makassar. The method used is research and development (R&D) with an adapted Borg & Gall model. The subjects of the study consisted of 30 grade XI students who actively participated in PJOK lessons and PJOK teachers as supporting informants. Data collection techniques include participant observation, interviews, student response questionnaires, documentation, and badminton skills tests. The results of the model development went through several stages, starting from preliminary studies, planning, initial product development, limited trials, revisions, expert validation, to large-scale trials. The results of the large-scale trial showed an increase in active student participation of 83%, exceeding the minimum target of 75%. The increase in basic badminton technique skills reached 75% with an average test score increasing from 60.5 to 78.3. The responses of students and teachers to the learning model were in the “good” and “very good” categories with an average questionnaire score of 4.3 and 4.2. Statistical analysis showed significant results (p < 0.05) in increasing student participation and skills. This model is effective in increasing student motivation and engagement during PJOK learning. Recommendations are given for this model to be implemented more widely to support more innovative and contextual learning.